Art activities for the socially alienated children in the intermediate grades - Sinay, Otelia G. (1972)
The study presents some activities in Art Education for the normalization and effective learning of socially-alienated children. The integrative method was used in the study. The therapeutic effect of art activities on children with behavioral problems has been supported by research studies on children's art. The reasearch found out that appropriate art activities offer opportunities for the emotional release of harbored feelings and aspirations, and that the satisfaction gained from accomplishment leads the socially-alienated children to attempt newer investigations and creative expressions. Their intrinsic reward is the joy of discovery and fulfillment.
Thesis (Master of Arts in Teaching - Special Education : Behavior Problems)--University of the Philippines, Diliman.
Keywords: Children with social disabilities -- Education (Elementary) -- Philippines; Art -- Study and teaching (Elementary) -- Activity programs -- Philippines